Webster's New World children's dictionary - Agnes, Michael (New York : Hungry Minds, 1999)
An illustrated dictionary, featuring selected word histories, synonym studies, lists of words with prefixes or suffixes, and spelling tips.
'A Webster's New World book'--T.p. verso.
Keywords: English language -- Dictionaries, Juvenile